Perfil de crescimento da nova linhagem de mucor subtilissimus (UCP 1262) e produção de quitosana em diferentes meios de cultivo - Carvalho, Ana Carla Rocha de (2017)
Chitin and chitosan are co-polymers with great biotechnological applications today (in the food industry, biotechnology, materials science, drugs and pharmaceuticals, agriculture and environmental protection among others) and, can be obtained from filamentous fungus from biomass. In this sense, the growth profile of the new strain of Mucor subtilissimus and chitosan production was investigated in divers culture media using alternative substrates (glucose and soya extract), in combination. The growth of M. subitilissimus was evaluated in four different culture media (Extract Malt, Extract Soy, Sabouraud Dextrose Agar and Synthetic Environment for Mucorales), as well as the Index Growth Rate Mycelial (MIGS), growth rate and generation time. The selected medium plus alternate substrates was used for the production of biomass and chitosan. The results showed a growth rate M. subtilissimus of μEsp.h-1 0.035831 and 0.033431, with generation time 19,34504h-1 and 20.73360 h-1, respectively, to medium Extract soybean and Medium Synthetic Mucorales for being selected the medium with soy extract to be more economical. The results were statistically validated and can be verified by the results of the ANOVA Table, Pareto Diagram and Surface Graph showing that the combination glucose soy extract increases the production of biomass and chitosan. The absorption spectrum of the infrared ray confirmed the polymer extracted chitosan with the degree of deacetylation of 78.3 % and 87.5 % respectively for the conditions of 2 trials is 4. The bioprocess performed showed high potential M. subtilissimus the biotransformation alternate substrates in effective production of chitosan with low cost and excellent degree of deacetylation as regards the microbiological chitosan.